Sternal Morphometry Of Common Myna (Acridotheres Tristis), Himalayan Bulbul (Pyconotus Leucogenys) And House Sparrow (Passer Domesticus) (Applied Biological Research, 2017)
The present study was conducted on Indian mynah, bulbul and sparrow with the  aim to study their gross morphological features of sternum. Birds, three each of  mynah, bulbul and sparrow, were collected dead and processed in air-tight jars,  for 3 weeks. Morphometric measurements of sternum were carried out using  standard methods. The study revealed that the anterior two-third of body in the  sternum of mynah, unlike the posterior one-third, had a distinctly designed  median groove. The sternal body in sparrow was divided into a concave anterior  half and a flat posterior half. The lengths and width of sternum were highest in  mynah. The length of sternum was nearly double the width in all three birds. The  dorsal surface of sternum in bulbul, as compared to mynah and sparrow, was  characteristically enriched by median pneumatic foramina. The rostrum was  typically ‘Y’ shaped. The lateral border of sternum on either side displayed 5, 5 and 4 costal facets in mynah, bulbul and sparrow, respectively. The sternal keel  was highly developed in all the 3 species of birds. The presence of highly  developed keel is indication for strong flight capability of these birds. The study  suggests that the presence of ՙY՚ shaped rostrum is a significant feature of  passerine birds.
Keywords: Passerine birds; sternum; morphometry